Absorption Rate of Industrial Program Vocational High School Students to the World of Work - Mulyanto; Widodo, Eko Nugroho (Universitas Pendidikan Ganesha, 2023)
The development of industrial technology today is very fast. However, SMK, as a ready-to-work workforce, not all have good readiness to meet the needs of the industrial world of work. This study aims to analyze the planning, implementation, evaluation, and absorption of students in the industrial class. This study used a qualitative approach with interviews, observation, and documentation techniques. The subjects involved in this study were school principals at the vocational education level. The data collection technique used in qualitative research is triangulation, namely the use of several different data sources to ensure the validity of the data obtained. Data collection was carried out by collecting data from various sources, such as interviews, observations, and document studies, with research instruments in the form of observation and interview guidelines. Data analysis includes two things, namely the implementation of analysis before in the field and analysis during the field. The results showed that industrial class planning had been carried out well, with curriculum synchronization, street vendor students, apprentice teachers, and guest teachers. Evaluation of activities is carried out periodically every 1 year. Student absorption in the 1st SMK industry reaches 94% at PT Alfamart, while the 2nd SMK is only absorbed 50%, with 30% at PT Daihatsu and 20% in other industries. Thus, the industrial class program at SMK has been successfully implemented properly. The implication of the results of this research is that stakeholders, such as schools, government and industry.